The Dissemination and Provision of Interfaith COVID-19 Vaccinations in Sikka Regency: Sosialisasi dan Pemberian Vaksinasi COVID-19 Lintas Agama di Kabupaten Sikka - S. Sahlan; Pujianti B. Donuata; Erwin Prasetyo (Yayasan Ahmar Cendekia Indonesia, 2022)
The COVID-19 pandemic that has hit Indonesia has had a very significant impact on all aspects of people's lives. COVID-19 (corona virus disease 19) is an infectious disease caused by a respiratory infection. Some of the efforts made by the government include large-scale and micro-scale social restrictions so that the government carries out socialization. Socialization is an effort to accommodate and provide information related to our goals and objectives, socialization is carried out as an effort to provide information to the public. With this information, the public no longer hesitates to carry out the COVID-19 vaccination. This outreach activity is carried out through social media. And for the provision of interfaith COVID-19 Vaccination held on the campus of IKIP Muhammadiyah Maumere, the aim is to increase the body's immunity by activating antibodies in the body so that it can reduce the impact of the transmission of COVID-19 disease and as an effort to stop the spread of COVID-19. The COVID-19 vaccination activity involves health workers, volunteers, elements of the TNI and Polri, the COVID-19 Task Force and the general public. The reason for being vaccinated is to support the government's program in the priority of COVID-19 vaccination targets, to help the government which is struggling to deal with COVID-19 in the country. This community service activity, which was recorded at the IKIP Muhammadiyah Maumere Campus, obtained 95% of the vaccination target had been achieved in the first dose of vaccination. In the 2nd dose of vaccination, the achievement of vaccination was only 80% of the target. So that the results of the activity showed that there was an increase in participants' knowledge about the effectiveness of the Covid-19 vaccine, and there was a change in participants' attitudes about their readiness to get the Covid-19 vaccination from unwilling and hesitant to willing. Abstrak Pandemic COVID-19 yang telah melanda Indonesia menimbulkan dampak yang sangat signifikan pada seluruh aspek kehidupan masyarakat. COVID-19 (corona virus disease 19) yaitu penyakit menular yang dimana disebabkan oleh infeksi saluran pernapasan. Beberapa upaya dilakukan pemerintah meliputi pembatasan sosial skala besar dan skala mikro sehingga pemerintah melakukan sosialisasi. Sosialisasi merupakan salah satu upaya untuk mengakomodir dan memberikan informasi terkait dengan maksud dan tujuan kita, sosialisasi di lakukan sebagai bentuk upaya memberikan informasi kepada khalayak. Dengan adanya informasi tersebut masyarakat tidak lagi ragu untuk melaksanakan vaksinasi COVID-19. Kegiatan sosialisasi ini dilakukan melalui media sosial. Dan untuk pemberian Vaksinasi COVID-19 lintas Agama diselenggarakan di halaman Kampus IKIP Muhammadiyah Maumere bertujuan untuk meningkatkan imunitas tubuh dengan mengaktifkan antibodi dalam tubuh supaya dapat mengurangi dampak dari penularan Penyakit COVID-19 dan sebagai upaya memutus penyebaran penyakit COVID-19. Kegiatan pemberian vaksinasi COVID-19 melibatkan tenaga kesehatan, relawan, unsur TNI dan Polri, Satuan Tugas COVID-19 dan masyarakat umum. Alasan diberikan vaksinisasi adalah mendukung program pemerintah dalam prioritas sasaran vaksinasi COVID-19, membantu pemerintah yang tengah berjuang menangani COVID-19 di Tanah air. Hasil dari kegiatan pengabdian masyarakat ini yang tercatat di Kampus IKIP Muhammadiyah Maumere diperoleh 95% dari target vaksinasi sudah tercapai di vaksinasi dosis pertama. Pada kegiatan vaksinasi dosis 2 pencapaian vaksinasi hanya 80% dari target